Novel double-layer structure negative pole piece and preparation method thereof

By introducing platinum nanoparticles into the negative electrode sheet of the silicon oxygen material to form a lithium platinum alloy, the problem of volume expansion of the silicon negative electrode material is solved, and higher energy density and safety performance are achieved.

CN119725402APending Publication Date: 2025-03-28龙子湖新能源实验室 +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411876536.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Silicon anode material will experience nearly 300% volume expansion during the process of lithium ions embedded and disengagement, which seriously restricts its commercial application.

Method used

A gradient structure silicon oxygen material negative electrode sheet is used, and a small amount of platinum nanoparticles are introduced into the bottom layer. Through the superior electron conductivity and lithium affinity of the platinum nanoparticles, a lithium platinum alloy is formed, which improves the electron transfer speed and adjusts the deposition position of lithium ions.

Benefits of technology

Without sacrificing battery safety, higher energy density is achieved, the battery discharge capacity is increased, the polarization phenomenon is reduced, and the battery safety performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725402A_ABST
    Figure CN119725402A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: adding a silicon-oxygen active substance, platinum nanoparticles, a conductive agent and a binder into a proper amount of solvent according to a certain proportion, mixing and uniformly stirring to obtain a negative electrode coating slurry A; coating a negative electrode current collector with the negative electrode coating slurry A to form a first coating; adding a silica active substance, a conductive agent and a binder into a proper amount of solvent according to a certain proportion, mixing and uniformly stirring to obtain negative electrode coating slurry B; coating the negative electrode coating slurry B on the first coating layer to form a second coating layer; and drying to obtain the double-layer structure negative pole piece. By adopting a double-layer coating technology, the safety performance of the battery can be remarkably improved. Through guidance of the platinum particles, excessive deposition of lithium on the bottom layer can be realized, and formation of lithium dendrites on the surface of the upper layer of the negative pole piece is avoided, so that the lithium dendrites are prevented from puncturing the diaphragm, a small amount of platinum nanoparticles are introduced into the negative pole piece, and the volume energy density of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery preparation, and particularly relates to a novel double-layer structure negative electrode sheet and a preparation method thereof. Background Art

[0002] The negative electrode material plays a crucial role in key performance indicators such as the safety, energy density, and cycle life of lithium batteries. With the increasing demand for driving range in new energy vehicles, lithium battery negative electrode materials are evolving towards high specific capacity. Although graphite negative electrode materials are known for their high conductivity and stability, the improvement of their specific capacity per gram has approached the theoretical limit (372 mAh / g). In contrast, silicon has a theoretical specific capacity as high as 4200 mAh / g, which far exceeds that of graphite-based negative electrode materials and makes it the highest-capacity option among known negative electrode materials. With the continuous trend of increasing battery energy density, silicon negative electrode materials are expected to become the main direction of future development.

[0003] During the process of lithium ion insertion and extraction, the silicon negative electrode material will experience a volume expansion of nearly 300%, which severely restricts the commercial application of silicon negative electrode materials. In current commercial practices, silicon negative electrode materials are usually combined with artificial graphite through doping technology, and silicon-carbon and silicon-oxygen are two mainstream technical paths. Silicon-carbon negative electrodes involve the mixing of nano-silicon and graphite materials, while silicon-oxygen negative electrodes are composites of silicon monoxide and graphite materials.

[0004] CN 118588907 A discloses a negative electrode film layer, a negative electrode sheet, a secondary battery, and an electrical device. The negative electrode film layer includes a first active material layer and a second active material layer arranged in a stacked manner. The material of the first active material layer includes a first silicon-oxygen material, and the material of the second active material layer includes a second silicon-oxygen material; the chemical formula of the first silicon-oxygen material is SixOy, and the chemical formula of the second silicon-oxygen material is SimOn, where x < y and m > n. The negative electrode film layer of the present disclosure has a double-layer active material structure, and the silicon-oxygen materials in the two active material layers have different silicon-oxygen atom quantity relationships. The negative electrode sheet prepared using this negative electrode film layer is beneficial to improving the stability of the electrode sheet of the secondary battery and exhibits excellent electrical performance and long-term performance while maintaining a high energy density.

[0005] CN 117117079 A discloses a lithium battery negative electrode sheet and its preparation method and application. The lithium battery negative electrode sheet provided by the present invention has the upper and lower surfaces of the current collector sequentially coated with a first coating close to the current collector surface and a second coating away from the current collector surface; the first coating and the second coating have the same surface density; the first coating and the second coating contain different conductive agent components and proportions. In the slurry mixing step, the conductivity difference of different coatings is solved by the distribution of the conductive agent ratio of the slurry, and the double-layer coating is used in equal proportions to solve the crystallization problem caused by the low lithium insertion rate of the coating. The application also provides a preparation method for a lithium battery negative electrode sheet, which is simple and easy to operate with good yield. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing a novel double-layer structured negative electrode sheet, which can effectively achieve higher energy density without sacrificing battery safety by preparing a gradient structured silicon-oxygen material negative electrode sheet. In the designed silicon-oxygen / graphite negative electrode, a small amount of platinum nanoparticles are incorporated into the bottom layer. During the lithium ion embedding process, due to the superior electronic conductivity and lithium affinity of the platinum nanoparticles, the excess Li+ successfully migrates to the bottom layer of the electrode sheet to form a lithium-platinum alloy. In the bottom layer containing platinum nanoparticles, the electronic conductivity of the anode increases, the electron transfer is accelerated, and the formation of a lithium-platinum alloy will also accelerate ion conduction.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] First, a one-pot solvothermal method was used with oleylamine as solvent, hexadecyltrimethylammonium bromide as reducing agent, and platinum acetylacetonate as metal precursor, followed by stirring and heating in a reactor to finally synthesize platinum nanoparticles.

[0009] A method for preparing a novel double-layer structured negative electrode sheet comprises the following steps:

[0010] (1) adding a silicon-oxygen active material, platinum nanoparticles, a conductive agent, and a binder to an appropriate amount of solvent in a certain proportion, mixing and stirring evenly to obtain a negative electrode coating slurry A; coating the negative electrode coating slurry A on the negative electrode current collector to form a first coating layer;

[0011] (2) adding a silicon-oxygen active material, a conductive agent, and a binder to an appropriate amount of solvent in a certain proportion, mixing and stirring evenly to obtain a negative electrode coating slurry B; applying the negative electrode coating slurry B on the first coating layer obtained in step (1) to form a second coating layer;

[0012] (3) After coating, the coating is dried to obtain a double-layer negative electrode sheet.

[0013] Furthermore, the silicon-oxygen active material is one or more of silicon-oxygen 400, silicon-oxygen 500, and silicon-oxygen 600.

[0014] Furthermore, the conductive agent is one or more of carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber, and carbon nanotubes.

[0015] Furthermore, the binder is one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate.

[0016] Furthermore, the solvent is one or more of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide.

[0017] Furthermore, the mass ratio of the silicon-oxygen active material, the conductive agent, and the binder is (90-98):(1-8):(3-7)

[0018] Furthermore, in step (1), the platinum nanoparticles account for 0.1% to 0.8% of the total mass of the silicon-oxygen active material, the conductive agent, and the binder.

[0019] Furthermore, the thickness of the first layer of coating in step (1) is 50 μm-200 μm.

[0020] Furthermore, the thickness of the second coating layer in step (2) is 50 μm-200 μm.

[0021] The present invention also provides a double-layer structured negative electrode plate made by the preparation method, the negative electrode plate is composed of a current collector and a first coating layer and a second coating layer arranged on the current collector, wherein only the first coating layer is embedded with platinum nanoparticles. The surface of the plate is relatively flat, and the upper and lower layers are also tightly combined.

[0022] The beneficial effects of the present invention are as follows: 1. A small amount of platinum nanoparticles are introduced into the negative electrode plate, and a lithium-platinum alloy is formed during the lithium ion embedding process. The discharge capacity of the battery is increased while the thickness of the plate remains unchanged, thereby improving the volume energy density of the battery. In addition, the formed platinum-lithium alloy has excellent electronic conductivity, accelerates the transmission speed of electrons, and reduces the polarization phenomenon of the battery.

[0023] 2. Double-layer coating technology can significantly improve the safety performance of batteries. Since platinum nanoparticles have excellent electronic conductivity and high affinity for lithium, they are selected as electroactive seeds to regulate the electric field distribution. The use of platinum particles helps regulate the lithium ion (Li + ) deposition position. Through the guidance of platinum particles, excessive lithium deposition can be achieved in the bottom layer, avoiding the formation of lithium dendrites on the upper surface of the negative electrode, thereby preventing lithium dendrites from piercing the diaphragm and causing thermal runaway of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 TEM image of synthesized platinum nanoparticles.

[0026] Figure 2 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode plate of Example 1 of the present invention.

[0027] Figure 3 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode plate of Example 2 of the present invention.

[0028] Figure 4 This is the first cycle charge and discharge curve of the button cell assembled with the negative electrode sheet of Example 3 of the present invention.

[0029] Figure 5 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode plate of Example 4 of the present invention.

[0030] Figure 6 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode sheet of comparative example 2 of the present invention.

[0031] Figure 7 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode plate of Example 5 of the present invention.

[0032] Figure 8 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode plate of Example 6 of the present invention.

[0033] Fig. 9 This is the first cycle charge and discharge curve of the button battery assembled with the negative electrode sheet of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0035] Preparation of platinum nanoparticles: 100 mg of platinum acetylacetonate and 300 mg of hexadecyltrimethylammonium bromide were added to 100 mL of oleylamine OAm and mixed evenly. The mixed solution was then placed in a polytetrafluoroethylene reactor, sealed with a stainless steel liner, and placed in an oil bath at 160°C, heated and stirred for 12 hours, then cooled to room temperature, the prepared black product was collected, washed twice with ethanol, and centrifuged at 5000 rpm for 5 minutes in a centrifuge to obtain platinum nanoparticles.

[0036] Example 1

[0037] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0038] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (according to the mass ratio of 95.9:1:2:1.1) and 0.5% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as a bottom layer;

[0039] (2) Then, a silica slurry without platinum nanoparticles (a negative electrode active material silica 400, a conductive agent superconducting carbon black, a binder sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 95.9:1:2:1.1) was coated on the bottom layer with a thickness of 100 μm as the top layer;

[0040] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0041] Example 2

[0042] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0043] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.4% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as a bottom layer;

[0044] (2) Then, an undoped silicon oxide slurry was coated on the bottom layer with a thickness of 100 μm as the top layer;

[0045] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0046] Example 3

[0047] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0048] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.6% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as a bottom layer;

[0049] (2) Then, an undoped silicon oxide slurry was coated on the bottom layer with a thickness of 100 μm as the top layer;

[0050] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0051] Example 4

[0052] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0053] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.8% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as a bottom layer;

[0054] (2) Then, an undoped silicon oxide slurry was coated on the bottom layer with a thickness of 100 μm as the top layer;

[0055] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0056] Example 5

[0057] A method for preparing a novel double-layer structured negative electrode sheet, the steps are as follows:

[0058] (1) A slurry made of silicon oxide as a negative electrode active material, superconducting carbon black as a conductive agent, sodium carboxymethyl cellulose as a binder, styrene-butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.2% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as a bottom layer;

[0059] (2) Apply undoped silicon oxide slurry on the bottom layer with a thickness of 100 μm as the top layer.

[0060] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0061] Example 6

[0062] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0063] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.5% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 50 μm using an adjustable scraper as a bottom layer;

[0064] (2) Then, an undoped silicon oxide slurry was coated on the bottom layer with a thickness of 50 μm as the top layer;

[0065] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0066] Example 7

[0067] The preparation method of the novel double-layer structure negative electrode sheet of this embodiment is as follows:

[0068] (1) A slurry made of the negative electrode active material silicon oxide 400, the conductive agent superconducting carbon black, the binder sodium carboxymethyl cellulose, styrene butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) and 0.5% platinum nanoparticles in deionized water was coated on a copper foil with a thickness of 200 μm using an adjustable scraper as a bottom layer;

[0069] (2) Then, an undoped silicon oxide slurry is coated on the bottom layer with a thickness of 200 μm as the top layer;

[0070] (3) After drying at 80°C for 12 hours, a double-layer composite silicon-oxygen negative electrode was obtained.

[0071] Comparative Example 1

[0072] A method for preparing a negative electrode sheet, the steps are as follows:

[0073] The slurry made of negative electrode active material silicon oxide, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose, and styrene-butadiene rubber (in a mass ratio of 95.9:1:2:1.1, respectively) was coated on a copper foil with a thickness of 100 μm using an adjustable scraper as the bottom layer; then a layer of silicon oxide slurry with the same ratio was coated on the bottom layer with a thickness of 100 μm as the top layer. After drying at 80°C for 12 hours, a double-layer composite silicon oxide negative electrode was obtained.

[0074] The negative electrode sheets prepared in Examples 1-7 and Comparative Example 1 were assembled into button-type batteries for performance testing. Lithium sheets were used as the electrodes. The test results are shown in Table 1.

[0075] Table 1 First cycle charge and discharge capacity of button cell

[0076] First lap charging capacity / mAh First cycle discharge capacity / mAh Example 1 9.343 8.544 Example 2 9.160 8.328 Example 3 9.270 8.417 Example 4 9.050 8.226 Example 5 8.683 7.974 Example 6 3.729 3.384 Example 7 11.855 10.881 Comparative Example 1 7.069 6.445

[0077] According to the data in Table 1, the mass percentages of platinum nanoparticles in Examples 1-5 are 0.5%, 0.4%, 0.6%, 0.8% and 0.2%, respectively, and the single-layer coating thickness of all samples is 100μm. Among these embodiments, the first-cycle discharge capacity of Example 1 is the highest, reaching 1.3 times the discharge capacity of Comparative Example 1. This shows that under the experimental conditions, 0.5% of platinum nanoparticles exhibit the best performance. Furthermore, the single-layer coating thicknesses of Examples 6 and 7 are 50μm and 200μm, respectively, which are 0.5 times and 2 times the coating thickness of 100μm in Example 1, respectively. In theory, the discharge capacity should be proportional to the coating thickness, but actual data show that the discharge capacity of Examples 6 and 7 is 0.4 times and 1.3 times that of Example 1, respectively, so 100μm is the optimal single-layer coating thickness. In summary, 0.5% of platinum nanoparticles and 100μm single-layer coating thickness in Example 1 constitute the best pole piece preparation solution.

[0078] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a novel double-layer structured negative electrode sheet, characterized in that The following steps are involved: (1) adding silicon-oxygen active material, platinum nanoparticles, conductive agent and binder into a proper amount of solvent in a certain proportion, mixing and stirring evenly to obtain negative electrode coating slurry A; coating the negative electrode coating slurry A on the negative electrode current collector to form a first coating layer; (2) adding a silicon-oxygen active material, a conductive agent, and a binder to an appropriate amount of solvent in a certain proportion, mixing and stirring evenly to obtain a negative electrode coating slurry B; applying the negative electrode coating slurry B on the first coating layer obtained in step (1) to form a second coating layer; (3) After coating, the coating is dried to obtain a double-layer negative electrode.

2. The method for preparing a novel double-layer structured negative electrode sheet according to claim 1, characterized in that: The silicon-oxygen active material is one or more of silicon-oxygen 400, silicon-oxygen 500, and silicon-oxygen 600.

3. The method for preparing a novel double-layer structure negative electrode sheet according to claim 1, characterized in that: The conductive agent is one or more of carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber, and carbon nanotubes.

4. The method for preparing a novel double-layer structured negative electrode sheet according to claim 1, characterized in that: The binder is one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and polyacrylate.

5. The method for preparing a novel double-layer structured negative electrode sheet according to claim 1, characterized in that: The solvent is one or more of deionized water, N-methylpyrrolidone and N,N-dimethylformamide.

6. The method for preparing a novel double-layer structure negative electrode sheet according to claim 1, characterized in that: The mass ratio of the silicon-oxygen active material, the conductive agent and the binder is (90-98): (1-8): (3-7).

7. The method for preparing a novel double-layer structured negative electrode sheet according to claim 1, characterized in that: In the step (1), the platinum nanoparticles account for 0.1% to 0.8% of the total mass of the silicon-oxygen active material, the conductive agent, and the binder.

8. The method for preparing a novel double-layer structured negative electrode sheet according to claim 1, characterized in that: The thickness of the first coating layer in step (1) is 50 μm-200 μm.

9. The method for preparing a novel double-layer structure negative electrode sheet according to claim 1, characterized in that: The thickness of the second coating layer in step (2) is 50 μm-200 μm.

10. A double-layer negative electrode sheet prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The negative electrode plate consists of a current collector and a first coating layer and a second coating layer arranged on the current collector, wherein only the first coating layer is embedded with platinum nanoparticles.

Citation Information

Patent Citations

  • Lithium battery negative plate as well as preparation method and application thereof

    CN117117079A

  • Negative electrode film layer, negative electrode pole piece, secondary battery and electric device

    CN118588907A

  • Silicon-based negative pole piece as well as preparation method and application thereof

    CN115000407A

  • Anode, lithium battery including anode, and method of preparing anode

    US20190198865A1

  • Rechargeable lithium battery including hybrid negative electrode and high concentration electrolyte

    US20240120462A1